Pediatric Lawnmower Injuries. Issue 12 (December 2017) - Lee, Tina S.; Luhmann, Jan D.; Luhmann, Scott J.; Quayle, Kimberly S.
Abstract : Objective: The aim of this study was to evaluate demographics, characteristics, and mechanisms of injuries caused by lawnmowers in children. Methods: Chart review from 1990 to 2010 at a level I pediatric trauma center identified patients younger than 18 years with lawnmower injuries. Demographics and characteristics of the injuries were analyzed by descriptive statistical analysis. Results: The study identified 88 subjects, with 80% males and 42% of the subjects younger than 5 years. When the lawnmower type was specified, riding lawnmowers caused the majority of injuries (72%). The most common mechanism of injury was related to slipping under lawnmower/being run over (51%). The most common injuries were lacerations (36%), fractures (27%), and amputations (22%); lower extremities were injured more frequently than other body areas (62%). The majority of patients (76%) required hospitalization with a mean length of stay (LOS) of 9.7 days and a mean number of procedures of 4. Complications included 6 infections, 1 tissue necrosis, and 1 death from hemorrhagic shock. Riding-lawnmower injuries were associated with younger children ( P < 0.0001). Riding lawnmowers and younger age were associated with longer hospital LOS ( P = 0.01, 0.006) and increased number of procedures ( P = 0.03, 0.003, respectively). Conclusions: Lawnmower injuries are still prevalent in children despite national safety recommendations. Injuries seen with riding lawnmowers were associated with younger age, higher number of procedures, longer LOS, and more severe injuries.